Fishermen community and livelihoods status of Kuala Nyalau, Bintulu, Sarawak - Mustafa Kamal, Abu Hena; Ismail, Johan; Idris, Mohd Hanafi; Rajaee, Amy Halimah; Sarker, S. M. Nurul Amin Harmuj Ali; Wong, Sing King; Gandaseca, Seca; Latif, Kamil; Mat Taib, Mimi Azwani; A. T., Nettley; T. F., Wendy; Hoque, M. M.; et al. (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2013)
Coastal artisanal fishery holds an important place in the socioeconomic improvement and livelihoods opportunity of the coastal community of Kuala Nyalau, Bintulu, Sarawak. It is documented as powerful income and employment generator as it motivates growth of a number of subsidiary businesses, and is a source of low-priced and healthy food. Socio-economic study results showed that the majorities (95%) of the community are fishermen, and fishing is the main activities followed by agriculture (palm oil and house hold orchard) and business. Fin fish is the main fishery item while about 100 types of fin fish species are caught and landed in this fisherman village round the year. Observation found that majority of the fishermen used the standard mesh size of nets to catch the fish like Parastromateus niger (black pomfret; 5 inches mesh), Euthynnus affinis (kawakawa ; 4 inches mesh), Scomberomorus commerson (mackerel; 4 inches mesh) and Rastralliger brachysoma (short body mackerel; 2.25 inches mesh). Studies on fisherman community also discovered that the catches using small pull net (pukat tarik; 1 inch mesh) by certain number of fishermen may have the negative impacts on the fishery resources in this coastal area. Therefore, more investigation is needed to know the impacts of pull net on fishery resources. In addition, the awareness activity among the fishermen on this destructive fishing activity could help to manage the fishery resources in the coastal environment of South China Sea.